The Use of Canva Learning Media to Improve the Learning Focus of Students with Special Needs at SLBN Balikpapan in the Subject of Flat Shapes - Rahayu Sri Waskitoningtyas; Sugianto Sugianto; Casmudi Casmudi (Department of Special Education, 2026)
The purpose of this study was to determine how the application of Canva learning media could improve the learning focus of students with special needs at SLBN Balikpapan with flat building materials. The study was conducted at SLBN Balikpapan using flat building materials. The research subjects were students at SLBN Balikpapan. This study was descriptive and qualitative. There were 22 students at SLBN Balikpapan who were the research subjects, using purposive sampling. The data collection methods were (1) observation, (2) interviews with 6 students and two teachers at SLBN Balikpapan, and (3) instruments/questionnaires regarding the use of Canva. The questionnaire was tested beforehand to prove its validity. Of the 25 questionnaires, 16 statements were deemed valid, and the reliability test was calculated using the Cronbach Alpha formula, yielding a reliability index of 73.76. Data analysis techniques included data reduction, data presentation, and conclusion drawing. For data validity, source triangulation was used. The questionnaire results regarding the use of Canva among SLB students showed an achievement rate of 81.22%. In conclusion, the use of Canva learning media at SLBN Balikpapan has contributed positively to improving the learning focus of students with special needs in flat shape subjects. Attractive and interactive visualizations make it easier for students to understand the material and actively participate in the learning process.